Indonesia’s Implementation in Migrant Workers Protection from Involvement Of Terrorism as ASEAN Member States - Achmad Yassin Zidan Akram Aslam (Journal of Law and Policy Transformation, 2024)
As the one of the largest sending and receiving states of migrant workers, ASEAN as an international organization with regional characteristics has objectives to protect the migrant workers from the threats of terrorism crimes. This happen because there are several cases of terrorism in ASEAN member states that involves migrant workers as the victims and as well as actor in their acts, some of them are Indonesian migrant workers. Thus, ASEAN and Indonesia need the measures to combating the challenges from acts of terrorism crimes which involves migrant workers. This research aims to examine the ASEAN and Indonesia as ASEAN member states approach to combating terrorism crimes and the enforcement of migrant workers protection from the threats. Therefore, the research uses normative legal research method by using statues and case approaches. The finding in this article is ASEAN and Indonesia took several measures in legal instruments regulation to combating terrorism crimes and to protect migrant workers from the involvement of terrorism acts.